2009
DOI: 10.1111/j.1442-2050.2009.00957.x
|View full text |Cite
|
Sign up to set email alerts
|

HIF-1α protein expression is associated with the environmental inflammatory reaction in Barrett's metaplasia

Abstract: The oxygen-regulated transcription factor subunit hypoxia inducible factor-1alpha (HIF-1alpha) is involved in angiogenesis, energy metabolism, cell survival, and inflammation. We examined the protein expression of HIF-1alpha within the progression of Barrett's sequence as well as the type and degree of the environmental inflammatory reaction. Squamous epithelium (SE), metaplastic, low- and high-grade dysplastic lesions, and tumor tissue of 57 resection specimens from patients with Barrett's adenocarcinoma were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 27 publications
0
15
0
Order By: Relevance
“…Expression was not further increased in dysplasia or OAC, implying that this may be an early change in neoplastic progression and in inflammation [58]. HIF-2α is increased in dysplasia and further increased in OAC, along with hypoxia-associated proteins VEGF and the erythropoietin receptor, while HIF-2α was not expressed in BO tissue, suggesting that this may be a later change in tumour development [59].…”
Section: Role Of Hypoxia and Oxidative Stressmentioning
confidence: 91%
“…Expression was not further increased in dysplasia or OAC, implying that this may be an early change in neoplastic progression and in inflammation [58]. HIF-2α is increased in dysplasia and further increased in OAC, along with hypoxia-associated proteins VEGF and the erythropoietin receptor, while HIF-2α was not expressed in BO tissue, suggesting that this may be a later change in tumour development [59].…”
Section: Role Of Hypoxia and Oxidative Stressmentioning
confidence: 91%
“…Nitric oxide can increase invasiveness of dysplastic and cancerous cells via regulation of MMPs and tissue inhibitor of metalloproteinases [87]. HIF-1a is increased in BE and correlates with the degree of inflammation, but since this does not increase in dysplasia and neoplasia, it is hypothesized to be an early event in neoplastic progression and inflammation [88]. HIF-2a on the other hand is increased in dysplasia and further in EAC, while it is not expressed in BE, suggesting that it is active later in the neoplastic process [89].…”
Section: Transcription Factors Mediate Tumor Promotion and Metastasismentioning
confidence: 97%
“…p53 also links inflammation with energy metabolism in an HIF1a-dependent interaction with TP53-inducible glycolysis and apoptosis regulator, a key mediator of glycolysis under hypoxic conditions [109]. Moreover, HIF1a protein expression is associated with the inflammatory processes in Barrett's metaplasia [88]. Therefore, further studies linking inflammation with energy metabolism through some of these pathways in the esophagus would enhance our understanding of the mechanisms involved in tumor progression and allow more accurate diagnosis of pre-neoplastic lesions more amenable to cancer development.…”
Section: Inflammation Induces Genomic Instabilitymentioning
confidence: 98%
“…To link the inhibitory actions of SIM on HIF-1α production with the statin actions on the capacity of tumor cells to support vital processes for tumor survival (12,32), 24 proteins involved in angiogenesis and inflammation were assessed in the present study ( Fig. 5 and Tables I and II).…”
Section: Discussionmentioning
confidence: 99%
“…To mimic hypoxia, B16.F10 melanoma cells were cultured in the presence of cobalt chloride (CoCl 2 ), a chemical inducer of HIF-1α stabilization (9,10). The mechanisms of cytotoxicity exerted by SIM on B16.F10 cells grown in the presence of the CoCl 2 were investigated with regard to tumor cell production of HIF-1α and expression of proteins involved in main tumorigenic processes coordinated by this protein, including angiogenesis and inflammation (11,12). Furthermore, as previous experimental data suggested that nuclear factor (NF)-κB can also induce overexpression of HIF-1α messenger RNA (13)(14)(15), the expression level of this protein was analyzed.…”
Section: Introductionmentioning
confidence: 99%